PEMITRA BAGI WILAYAH DESA PUCUNG, KECAMATAN EROMOKO KABUPATEN WONOGIRI - Priyono, Kuswaji Dwi; Sigit, Agus Anggoro; Priyono, Priyono; Ulinuha, Agus (WARTA, 2017)
Once the problem of clean water shortage is resolved, new problems arise related to the cost of treating water pumps and water distribution channels through uneven public hydrants. Through the Focus Group Discussion (FGD) activity conducted by UMS Community Service Team which was attended by all heads of Dusun and management of Air Tirta Gua Suruh, it has been formulated the need for productive business in groups related to water utilization which can be used as a joint result for contribution of water pump maintenance cost Cave Suruh. The need for daily vegetable ingredients will be fulfilled independently and group through vegetable crops of pollybag media. The result of the sale of vegetable business of PKK Group and Karangtaruna has added input to the water management cost of Suruh Cave. This PEMITRA UMS Programs in assisting the community to make media pollybag as well as vegetable seed business capital managed by PKK Group in Kangkung and Karangtaruna group in Wijil have been understood.